2020
DOI: 10.21501/22161201.3298
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de necesidades de apoyo en universitarios con diversidad funcional de origen físico: un estudio de caso

Abstract: Objetivo. Este estudio evaluó las necesidades de apoyo de estudiantes universitarios con diversidad funcional de origen físico en una Institución Educativa Superior. Se analizó, además, la percepción del docente y, en su conjunto, la correspondencia con las políticas de inclusión, tanto institucionales como de la nación. Método. Bajo el estudio de caso, se trabajó el enfoque cualitativo, con un diseño de teoría crítica. Se usó la entrevista en profundidad, el grupo focal y el análisis documental para la triang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This study, in the first place, observed that students with motor functional diversity found difficulties with the lack of inclusive architectural design in the university infrastructures because most of them are not fit for all, for example, restrooms, cafeterias, second- and third-floor classrooms, and some administrative areas; this result is similar to the study by Santos et al 13 As stated by Domínguez et al ., 14 people with motor functional diversity can be independent, as long as they have the means of accessibility to achieve it. Secondly, Toutain 15 indicates that the most-common barriers to adaptation are lack of knowledge by students about the resources of the campus and the inability to know the exact number of enrolled students who have a disability; similarly, Pérez et al, 16 mention in their systematic review that these were the difficulties most stated by the participants, which shows that this problem does not only occur in our country.…”
Section: Discussionmentioning
confidence: 99%
“…This study, in the first place, observed that students with motor functional diversity found difficulties with the lack of inclusive architectural design in the university infrastructures because most of them are not fit for all, for example, restrooms, cafeterias, second- and third-floor classrooms, and some administrative areas; this result is similar to the study by Santos et al 13 As stated by Domínguez et al ., 14 people with motor functional diversity can be independent, as long as they have the means of accessibility to achieve it. Secondly, Toutain 15 indicates that the most-common barriers to adaptation are lack of knowledge by students about the resources of the campus and the inability to know the exact number of enrolled students who have a disability; similarly, Pérez et al, 16 mention in their systematic review that these were the difficulties most stated by the participants, which shows that this problem does not only occur in our country.…”
Section: Discussionmentioning
confidence: 99%